Delivering TVET at the secondary level: A practical approach - Morris, Halden A.; Powell, Carole M. (School of Education, UWI, St. Augustine, 2013)
Secondary education can be regarded as the watershed of the education continuum, as it is positioned between compulsory primary education and the world of higher education, training, and work. Hence, curricular content at this level should be enriched and should be culturally sensitive towards the holistic and relevant development of learners. The scope to provide a complementary mix between academics and technical and vocational education and training (TVET) in order to respond to global demands is evident, and should be pursued in order to facilitate human capital development (HCD). Challenges envisioned and experienced in implementing such formidable curricula exist, nevertheless with smart engaging approaches it is believed that these can be overcome. This paper presents a practical approach piloted in Jamaica to facilitate the delivery of TVET in an economical manner. The approach emphasized gains in sharing upgraded resources for the delivery of TVET
Keywords: Technical and vocational education and training; Secondary education; Secondary school curriculum; Curriculum development; Curriculum implementation; Human resources development; Caribbean